Aplikasi Media Pembelajaran Pendidikan Agama Kristen Untuk Anak - Anak Sekolah Minggu Berbasis Android (Studi Kasus Gereja Toraja Jemaat Ora Et Labora Lagia) - Delvi Vebriyanti; Rinto Suppa; Solmin Paembonan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2022)
This review intends to plan and fabricate an Android-based Christian Strict Instruction Learning Media Application at the Ora Et Labora Lagia Toraja Church. The exploration strategy utilized is a subjective strategy with information assortment methods utilizing perception, meetings, and writing studies. This learning media application was created utilizing the Cascade Framework improvement technique. The product utilized in the plan and execution of the framework involves Adobe Streak Proficient CS6 as the framework plan. Christian strict training learning media applications incorporate Sunday school materials, tests, and youngsters' profound melodies. The application that has been assembled has been tried on clients so an application that runs well is acquired